Corrigendum to ‘Evidences and perspectives of the use of probiotics, prebiotics, synbiotics, and postbiotics as adjuvants for prevention and treatment of COVID-19: A bibliometric analysis and integrative review’ [Trends in Food Science & Technology 120 (2022) 174–192] (Trends in Food Science & Technology (2022) 120 (174–192), (S0924224421006907), (10.1016/j.tifs.2021.12.033)) - Xavier-Santos, Douglas; Padilha, Marina; Fabiano, Giovanna Alexandre; Vinderola, Gabriel; Cruz, Adriano Gomes; Sivieri, Katia [UNESP]; Costa Antunes, Adriane Elisabete (Elsevier, 2022)
The authors regret to inform that the reader should consider this article as a bibliometric and integrative review instead of a bibliometric and systematic review due to the methodological procedures followed. Introduction section: “This is an unprecedented study to identify the scientific perspectives of dietary interventions that may collaborate to immunomodulation and constrain the damage promoted by SARS-CoV-2 infection through a bibliometric analysis associated to a systematic review.” Should be replaced with: “This is an unprecedented study to identify the scientific perspectives of dietary interventions that may collaborate to immunomodulation and constrain the damage promoted by SARS-CoV-2 infection through a bibliometric analysis associated to an integrative review.” Methodology section: “Data collected in the Scopus database were then accomplished utilizing the VOSviewer v.1.6.17 (https://www.vosviewer.com/) in order to gather information related to countries network, co-occurrence networks of author keywords, and co-occurrence networks of terms in title/abstract. The data extracted from Scopus to obtain the terms present in titles and abstracts were processed utilizing binary counting without considering a repeated item in the same publication, according to the network view map. The software enables the elaboration of a map of co-occurrence terms from data exported in an Excel file format.” Should be replaced with: “Data collected in the Scopus database were then accomplished utilizing the VOSviewer v.1.6.17 (https://www.vosviewer.com/) in order to gather information related to countries network, co-occurrence networks of author keywords, and co-occurrence networks of terms in title/abstract. The data extracted from Scopus to obtain the terms present in titles and abstracts were processed utilizing binary counting without considering a repeated item in the same publication, according to the network view map. The software enables the elaboration of a map of co-occurrence terms from data exported in an Excel file format. The clinical trials registered and associated to the effects of probiotics and synbiotics in the prevention and therapy of COVID-19 were collected in the ClinicalTrials.gov database (https://clinicaltrials.gov/) and included in the integrative review.” Bibliometric analysis and scientific production section: “In this study, the bibliometric analysis reported above, provided as a basis for leading the systematic review, approached the topics of highest relevance for microbiome modulation by means of these supplements as an adjunctive therapy, safe, effective, and a low-cost strategy to support prevention or and treatment of COVID-19.” Should be replaced with: “In this study, the bibliometric analysis reported above, provided as a basis for leading the integrative review, approached the topics of highest relevance for microbiome modulation by means of these supplements as an adjunctive therapy, safe, effective, and a low-cost strategy to support prevention or and treatment of COVID-19.” Clinical evidence of probiotics to prevent or treat COVID-19 section: “An interesting retrospective study carried out on 800 COVID-positive patients with diarrhea supplemented with probiotics showed that the disease duration time in the patients that were supplemented with probiotics, was significantly shorter compared to the control group and the probiotics contributed to relieving patients’ abdominal distension, nausea, vomiting, and other gastrointestinal symptoms (Huaren & Zazhi, 2021).” Should be replaced with: “An interesting retrospective study carried out on 800 COVID-positive patients with diarrhea supplemented with probiotics showed that the disease duration time in the patients that were supplemented with probiotics, was significantly shorter compared to the control group and the probiotics contributed to relieving patients’ abdominal distension, nausea, vomiting, and other gastrointestinal symptoms (Ke & Zhang, 2020).” In the reference section: “Huaren, S., & Zazhi, X. (2021). World Chinese journal of digestology. https://www.wjgnet.com/1009-3079/. (Accessed August 22, 2021).” Should be replaced with: “Ke, E., & Zhang, H. (2020). Clinical effects of probiotics in ordinary-type COVID-19 patients with diarrhea. World Chinese Journal of Digestology, 28, 834–838.” Table 2 Studies registered in ClinicalTrials.gov database related to the effects of probiotics and synbiotics in the prevention and therapy of COVID-19. The Table 2 was updated with the addition of the study “NCT04368351”. Table 3 Evidence of clinical trials with probiotic strain in coronavirus disease: In Table 3, the correct citation is “Ke and Zhang (2020)” instead of “Huaren and Zazhi (2021)”. The authors would like to apologise for any inconvenience caused. Revised Table 2. Studies registered in ClinicalTrials.gov database related to the effects of probiotics and synbiotics in the prevention and therapy of COVID-19. [Table presented] Revised Table 3. Evidence of clinical trials with probiotic strain in coronavirus disease. [Table presented]